2016
DOI: 10.3343/alm.2016.36.2.124
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interactions of Antibiotic Combinations of Colistin, Tigecycline, and Doripenem Against Extensively Drug-Resistant and Multidrug-Resistant Acinetobacter baumannii

Abstract: BackgroundAcinetobacter baumannii infections are difficult to treat owing to the emergence of various antibiotic resistant isolates. Because treatment options are limited for multidrug-resistant (MDR) A. baumannii infection, the discovery of new therapies, including combination therapy, is required. We evaluated the synergistic activity of colistin, doripenem, and tigecycline combinations against extensively drug-resistant (XDR) A. baumannii and MDR A. baumannii.MethodsTime-kill assays were performed for 41 XD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 36 publications
1
29
1
4
Order By: Relevance
“…Thus, many recent studies have investigated combined therapy of two or more agents for MDR acintobacter infections. Specially combination regimen of Tigecycline or Colistin with other antibiotics have frequently been reported .Park and coworker found a high rate of in vitro synergy and bactericidal activity and lack of antagonism in combination of colistin and Doripenem (Park et al, 2016). As well as, recent study revealed a superior activity for combination of tigecycline with cefoperazone-sulbactam against MDR acintobacter (Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many recent studies have investigated combined therapy of two or more agents for MDR acintobacter infections. Specially combination regimen of Tigecycline or Colistin with other antibiotics have frequently been reported .Park and coworker found a high rate of in vitro synergy and bactericidal activity and lack of antagonism in combination of colistin and Doripenem (Park et al, 2016). As well as, recent study revealed a superior activity for combination of tigecycline with cefoperazone-sulbactam against MDR acintobacter (Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage of tigecycline is that it achieves low peak serum concentrations after administration of a standard 100 mg loading dose, which may increase the development of resistance during therapy 22,23. Studies investigating the antibiotic susceptibility of Acinetobacter species revealed that these bacteria are most susceptible to colistin and tigecycline, and a combination of these antibiotics has the lowest antagonistic interaction when compared to combinations of colistin or tigecycline with carbapenems 2,18,19. Taken together, these results indicated that combinations with colistin and tigecycline remain the best choice for the treatment of MDR Acinetobacter infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, relatively low rate of synergy of imipenem and the effect of CRAB strains showing a high MIC for meropenem (MIC ≥64 mg/L) might have influenced the overall results (40)(41)(42). The possibility of unexpected antagonistic effect and suboptimal doses of other antibiotics should lead to a cautious interpretation of the results on combination therapy (43,44). Taken together, a multidisciplinary approach by physicians and microbiologists to perform routine synergy tests to determine the appropriate combination therapy should be considered.…”
Section: Discussionmentioning
confidence: 99%